Penggunaan Media Papan Flanel untuk Meningkatkan Kemampuan Mengenal Huruf Vokal dan Konsonan pada Anak Kelompok B di TKK Rherhedja 2 - Maria Magadalena Mery (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
The research aims to: (1) know how to use the media on the flannel board in learning the recognition of vowels and consonants in group B TKK Rherhedja children. (2) Improve the ability of children in group B TKK Rherhedja 2 in recognizing vowels and consonants through the media flannel board. This research is a class action research (CAR), which is implemented in 2 cycles. The data collection techniques used are observation and documentation. The subject of this study was the children of group B at TTK Rherhedja 2 with a total of 18 people. The results of the research proved, (1) Media Flannel board already used well in learning to children group B in TTK Rherhedja 2. On cycle I, the percentage of applicability rate is 75% in good category and on cycle II increased to a very good category with a percentage of 95%. (2) Ability to recognize letters in group B Children in TKK Rherhedja 2 of the 18 children on the pre cycle, newly developed children were 6 peoples or 33.33%, children who started to grow were 9 peoples or 50%, children develop as expected were 3 peoples or 16.67% and very good child was 0%. After using the flannel board media, there was an increase in cycle I: children who were just developing 0%, children who were starting to develop were 6 peoples or 33.33%, children developing as expected were 12 peoples or 66,67%. In Cycle II there was an increase in the ability to recognize letters as follows: the percentage of children newly developing was 0%, the percentage of children starting to develop was 0%, the percentage of children developing as expected was 44.44% or 8 peoples, and very well developed children was 55.56% or 10 peoples. Thus, the Flannel Board Media can improve the ability of group B children in recognizing vowels and consonants in TKK Rherhedja